Penemuan Hukum oleh Hakim di Indonesia: Dasar, Metode, serta Implikasinya terhadap Kepastian dan Keadilan Hukum - Hidayat, Agi Attaubah; Sururi, Ramdani Wahyu; Anwari, Amalia Nur; Sugiarti, Lilis Diah; Ikhsan, Fachrial; Fauzi, Ridwan (IAIN Langsa, 2025)
Ideally, legal discovery by judges is expected to create both legal certainty and substantive justice simultaneously. However, in reality, the practice of legal discovery in Indonesia often leads to legal uncertainty due to differences in interpretation and the varied use of interpretative methods. Flexibility in legal discovery also has the potential to be misused if not supported by ethical foundations and adequate competence. This study aims to analyze the legal basis, methods, and implications of legal discovery by judges in Indonesia on legal certainty and justice. This research employs a juridical-normative approach by analyzing Law No. 48 of 2009, court decisions, and legal doctrines related to methods of legal interpretation. The results show that legal discovery by judges is necessary to address legal gaps and adapt the law to social developments. However, flexibility in legal discovery must be balanced with consistency in legal application to maintain legal certainty.